Analysis of influence of steam-turbine cycle basic parameters on the efficiency of triple combined-cycle plants - N. N. Galashov; S. A. Tsibulsky (Известия Томского политехнического университета: Инжиниринг георесурсов, 2009)
The profile of the advanced triple cycle steam-gas plant has been selected. The authors have developed the mathematical model for calculating the indicators of triple cycle steam-gas plant. The influence of the basic parameters of the binary steam-turbine cycle with steam-water and butane working bodies on the efficiency and capacity of a steam-gas plant with electric and gas turbine-driven pumps was analyzed. The investigations demonstrate that net efficiency above 60 % can be obtained on steam-gas plant with a gas-turbine installation SGT5-8000H. The increase of steam initial pressure, initial temperature of open steam and reheat steam; reduction condensation temperature of halocarbon and temperature of gases escaping a waste-heat boiler as well as steam intermediate pressure cylinder affect positively on increase of the efficiency and capacity of a steam-gas plant. The replacement of pump electric drive by a gas-turbine drive allows increasing a steam-gas plant net power by approximately 30 MW and nearly reducing auxiliary power.